Meningkatkan Pengetahuan Branding UMKM Makanan dengan Pemanfaatan Teknologi Artificial Intelligence - Anshor, Abdul Halim; Sulaeman, Asep Arwan; Rezeki, Fitri; Raharjo, sugeng budi (DPPM Universitas Pelita Bangsa, 2024)
Micro, small, and medium enterprises (MSMEs) in the food sector are one of the important sectors in the Indonesian economy. However, many food MSMEs still face branding obstacles, making it difficult to compete in the market. Artificial intelligence (AI) technology can help improve brand knowledge for food MSMEs. This study aims to expand the brand knowledge of food MSMEs through the use of AI technology. This study was conducted using a seminar activity method as a form of socialization and assistance for partners. Training and assistance focused on the use of AI tools for branding such as, Social media analysis which aims to understand customer sentiment and market trends. Chatbots to provide better customer service and increase sales conversions. Targeted advertising aims to reach the right customers with the right message. Research shows that training and assistance using AI technology can significantly improve the brand knowledge of food MSMEs. This study contributes to expanding knowledge about food branding of MSMEs in Indonesia. The results of this study can be used by other food MSMEs to increase their competitiveness in the market.